Smart Learning of Distance Learning Process Based on Website - H Irmayanti; I T Rahman; L H Nurri; F Khairudin; N P Dewi (International Journal of Education, Information Technology, and Others, 2021)
This research aims to analyze e-learning that can make it easier for teachers and students to carry out teaching and learning activities without limitation of time and place. The method used descriptive qualitative. The results obtained from this study are an application that can be used for remote teaching and learning activities, the teacher can enter the material into the application as well as students can access the material anytime and anywhere, besides that teachers and students can still communicate synchronously even without face to face. These results are obtained from the application development process starting from system requirements analysis, software design, application coding, application implementation, application testing, and application maintenance. This study's results can help teaching and learning activities during the Covid-19 pandemic as it is today. The impact is that students can still get lessons according to the curriculum of each level of education, and teachers can still share knowledge with all their students even though they cannot do face-to-face learning